Formulation of H2 and H(infinity) power deficit estimation method for isolated power system - Jamri, Mohd Saifuzam (2024)
An isolated power system network is described as an electrical network that is not connected to the larger power system grid. It was defined as a local electrical network comprising an isolation generator and transformer with branch circuits designed for certain applications. The local generator in an isolated power system network is basically used as the main source. The network is very sensitive to the sudden high equilibrium condition of electrical load demand that can lead to unbalanced power, delayed load performance, overloaded circuits, and severe frequency deviation problems. The undesired frequency response can harm the connected load, damage the protection devices, and cause the network to trip and experience a total blackout. According to the literature review, the rate of frequency deviations gives implicit information about the system’s stability. There is an advantage to knowing the magnitude of the power deficit of the network by only observing the system’s frequency behaviour. Hence, the main objective of this research is to observe and monitor the power deficit for isolated electrical network conditions through system frequency observation. In this research, the similarities between the structure of